(untitled) (Journal of Social Sciences Review, 2023)
The digital divide, characterized by disparities in access to and use of technology, presents a significant challenge in education. This study aims to investigate the impact of the digital divide on students’ access to technology and its influence on their educational outcomes. A quantitative research methodology was employed, with a sample size of 400 students from diverse educational backgrounds. The study utilized survey questionnaires to gather data on internet access, device ownership, and technology use in education. The findings revealed variations in internet access across different age groups, with younger individuals having higher levels of access compared to older age groups. Additionally, disparities in household internet access were observed between rural and urban areas, with rural areas experiencing lower connectivity. Gender-based differences in personal device ownership were also evident, highlighting potential gender-related digital divides. Moreover, students from low-income households faced lower levels of internet access, indicating a socioeconomic divide in technology access. Additionally, the study emphasizes the importance of establishing technology resource centers in schools and fostering public-private partnerships to bridge the technology gap in education. The study contributes to the existing body of knowledge by providing insights into the digital divide and offering recommendations for addressing this issue in the field of education.